Rapid and Simultaneous Determination of the Iodine Value and Saponification Number of Edible Oils by FTIR Spectroscopy. Issue 4 (8th February 2018) - Xu, Lirong; Zhu, Xufei; Yu, Xiuzhu; Huyan, Zongyao; Wang, Xingguo
Abstract : A rapid method is developed to facilitate the Fourier transform infrared (FTIR) spectroscopy analysis of edible oils using disposable polyethylene (PE) films as sample support for the determination of the iodine value (IV) and saponification number (SN). For direct IV analysis, quantification is achieved using the cis and trans double band region (3206–2992 cm −1 ) by a partial least squares calibration model, whereas, SN is directly determined using the area in carbon chain skeleton vibration absorption region (781–650 cm −1 ). The proposed method is applicable to various edible oils ranging in IV from 7.0 to 190.0 g 100 g −1 and SN from 162.7 to 222.0 mg g −1 with good precision and accuracy (relative standard deviations 0.39 and 0.32%, respectively) relative to the AOCS standard methods but with markedly less sample preparation and analytical effort. Practical Applications : Standard titration methods for determining the IV and SN of edible oils are labor intensive and require complex solvents and reagents. The PE‐film‐based FTIR method is more sensitive than attenuated total reflectance‐FTIR method and free from problems associated with the viscosity of oils, which is practical and easy to operate. The method can further simplify and facilitate simultaneous FTIR IV and SN analyses and is applicable to various edible oils over a wide range. A PE‐film‐based FTIR method is developed to determine the iodine value (IV) and saponification number (SN) of edible oils. The regions 3206–2992 cm −1 and 781–650 cm −1 are selected for IV and SN analysis, respectively. In the graphical abstract the IV and SN calibration and validation figures are presented. Abstract : A PE‐film‐based FTIR method is developed to determine the iodine value (IV) and saponification number (SN) of edible oils. The regions 3206–2992 cm −1 and 781–650 cm −1 are selected for IV and SN analysis, respectively. In the graphical abstract the IV and SN calibration and validation figures are presented.